Pengembangan Komik Sains Terintegrasi Literasi Lingkungan pada Topik Mitigasi Bencana Banjir - Aini, Kurrotul; Hadi, Wiwin Puspita; Yasir, Mochammad; Rakhmawan, Aditya; Sutardja, Maria Chandra (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
An understanding of environmental literacy needs to be implemented as a form of awareness of caring for the environment, one of which is in terms of flood disaster mitigation. Comics is a learning medium that presents material in the form of illustrated stories to make it more interesting, fun, not boring and easy for students to understand. The purpose of this study was to determine the feasibility of science comics, as well as the readability and responses of students to science comic media. This study uses the ADDIE development model starting from the analysis, design, development, implementation, and evaluation stages. The sample used in this study was students of class VII MTs Raudlatul Ulum who were randomly selected. Based on the research that has been done, the results are: 1) Science comic media obtains a material validation score of 84% and media validation obtains a score of 93% with a very valid category. 2) Comic media obtained a readability score of 81.4% in the very good category 3) Student responses to comic media obtained a score of 82% in the very good category. Based on these results it can be seen that science comic media is categorized as very valid so it is suitable for use as a learning medium.